The effects of government spending in a small open economy within a monetary union - Daragh Clancy; Pascal Jacquinot; Matija Lozej (European Central Bank (ECB), 2014)
Small open economies within a monetary union have a limited range of stabilisation tools, as area-wide nominal interest and exchange rates do not respond to country-specific shocks. Such limitations imply that imbalances can be difficult to resolve. We assess the role that government spending can play in mitigating this issue using a global DSGE model, with an extensive fiscal sector allowing for a rich set of transmission channels. We find that complementarities between government and private consumption can substantially increase spending multipliers. Government investment, by raising productive public capital, improves external competitiveness and counteracts external imbalances. An ex-ante budget-neutral switch of government expenditure towards investment has beneficial effects in the medium run, while short-run effects depend on the degree of co-movement between private and government consumption. Finally, spillovers from a fiscal stimulus in one region of a monetary union depend on trade linkages and can be sizeable.
Keywords: E22; E62; H54; 330; fiscal policy; imbalances; public capital; trade